Sea buckthorn pulp and seed oils ameliorate lipid metabolism disorders and modulate gut microbiota in C57BL/6J mice on high-fat diet - Wang, Zhen; Zhou, Shengmin; Jiang, Yuanrong (Frontiers in Nutrition, 2022)
Introduction Non-alcoholic fatty liver diseases (NAFLD), along with the complications of obesity and dyslipidemia, are worldwide lipid metabolism disorders. Recent evidence showed that NAFLD could be ameliorated by diet and lifestyles by attenuating gut microbiota dysbiosis via the gut–liver axis. Sea buckthorn oils, including sea buckthorn pulp oil (SBPO) and sea buckthorn seed oil (SBSO), were investigated in this study for their beneficial effects on gut–liver axis in C57BL/6J mice on a high-fat diet. Methods Sixty of male C57BL/6J mice were assigned into five groups, fed with low-fat diet containing soybean oil (SO), high-fat diet comprising lard oil (LO), peanut oil (PO), SBSO or SBPO, respectively, for 12 weeks. Serum and hepatic biochemical analysis, liver and perirenal fat histological analysis, and fecal 16S rRNA gene sequencing were conducted to reflect the influence of five diets on gut-liver axis. Results Dietary SBPO reduced visceral fat accumulation, adipose cell size, serum and hepatic triglyceride, LDL-C levels, and hepatic cell damage score; increased gut microbiota diversity with a higher abundance of Lactobacillus, Roseburia, and Oscillibacter compared with PO. SBSO showed equal or weaker effects compared to SBPO. Conclusion This study demonstrates that dietary SBPO has the potential to ameliorate NAFLD and related metabolic disorders, like obesity and dyslipidemia, by modulating gut microbiota.